Динамічні характеристики вимірювальних перетворювачів на базі штучних нейронних мереж при застосуванні адаптивного алгоритму - Фоменко, В. Д.; Пахомова, А. О. (ХНУРЕ, 2019)
Application of adaptive identification method dynamiccharacteristics of measuring instruments by impulse characteristics based on artificial neural networks. At present, artificial neural networks (INS) that are capable of learning from existing data are used to solve many metrological problems. The purpose of this work subsection is the development and application of an adaptive method based on the INS for identifying SIT parameters modeled by dynamic links of the aperiodic and vibrational types according to impulse characteristics.